Dualidade em teoria de campos - Silva, Roberto Menezes da (2003)
This work have as principal objecitve the issue of duality in topological theories We discurse the method of gauge embedding, that is used for dual mapping. We investigate dual theories with Abordaremos dualidade com teorias B ? F, in 3 + 1, free, with matter and nonlinearity.